Control and optimization of continuous chromatographic separation processes - Bijan Medi (2012)
The modern trend of pharmaceutical technology has been greatly shifted towards single or pure enantiomeric drugs due to strict regulations imposed by drug approval authorities in order to obtain higher drug efficiency and to alleviate undesirable side effects. Enantiopure compounds can be accessed either by organic synthesis or by resolution techniques. Recently, chromatographic separation has become the preferred method for its cost effectiveness, ease of operation, and flexibility as it employs variety of processing materials and methods supported by rich theoretical background. Simulated moving bed (SMB) has been extensively used for the separation of chemicals in the past 50 years, though its application to enantioseparation is relatively new. Supported by the benefits of counter-current mode of operation, SMB has become the method of choice for large-scale operations. However, SMB is a complex process both in terms of design and operation. There have been numerous efforts to emulate SMB by simpler processes. Many of them are based on using a single column with a recycle stream. In this work, we proposed an improved single-column chromatographic (ISCC) separation process. The term `improved' refers to both conceptual and physical modifications. We proposed a novel fraction collection scheme and allowed overlapped peaks from adjacent cycles. We also modified the fraction collection mechanism in order to facilitate online monitoring. Another advantage of the ISCC process is its large degree of freedom as injection volume, cycle time, desorbent flow rate, feed concentration and fraction-collection intervals can all be decision variables in this process. Every continuous process needs some sort of feedback from the process for quality control and monitoring. The chromatographic separation processes are usually monitored via low-frequency devices such as analytical high-performance liquid chromatography (HPLC) systems. Alternatively, innovative approaches have been taken to improve the sampling rate using combination of various detectors, peak deconvolution, etc. The design of an efficient online monitoring system is still an open problem. In this work, we proposed an online monitoring system, which comprises of two parallel HPLC units with customized peripherals in order to improve the accuracy and sampling rate. The proposed device can be readily coupled to the ISCC process. It is also less expensive compared to the similar commercial units. Minimizing operation costs and maximizing productivity are necessary for a profitable operation. They are typically complex functions of process inputs, and the operation might be limited by certain constraints as well. Similarly, optimization is not straightforward for the ISCC process as there are several variables contributing to a multi-dimensional solution space. On the other hand, process outputs have opposing effects on the profitability of the process. As a result, there may not be a single dominating solution as the best operating point.